Fabrication and kW‐level MOPA laser output of planar waveguide YAG/Yb:YAG/YAG ceramic slab. Issue 4 (11th September 2018) - Jiang, Nan; Lin, Weiping; Zhao, Yu; Wang, Juntao; Gao, Qingsong; Qu, Haiyun; Ge, Lin; Xie, Tengfei; Liu, Qiang; Pan, Yubai; Li, Jiang
Abstract: Using the tape casting method combined with vacuum sintering and hot isostatic pressing, high‐quality planar waveguide YAG/10 at.%Yb:YAG/YAG ceramics were successfully prepared. For the sample presintered at 1750°C for 30 hours and then HIPed at 1700°C for 3 hours in 200 MPa argon, the in‐line transmittance reached 82.5% at 400 nm and the average grain size was ~17.1 μm. The diffusion behaviors of Yb ions across the contact boundary between the cladding YAG layer and the core Yb:YAG layer were determined by Fick's second law. Then, a 1030 nm continuous‐wave (CW) Yb:YAG planar waveguide ceramic laser based on the structure of master oscillator power amplification (MOPA) was realized. After a single‐pass amplification, the maximum output of the ceramic slab (60 × 10 × 1 mm 3 ) reached 1251 W and the corresponding optical‐to‐optical efficiency was 30.0%, which is the highest output power of a Yb:YAG planar waveguide ceramic laser to the best of our knowledge.